Lethal Interaction of Nuclear and Mitochondrial Genotypes in Drosophila melanogaster. Issue 7 (1st July 2019) - Salminen, Tiina S; Cannino, Giuseppe; Oliveira, Marcos T; Lillsunde, Päivi; Jacobs, Howard T; Kaguni, Laurie S
Abstract: Drosophila melanogaster, like most animal species, displays considerable genetic variation in both nuclear and mitochondrial DNA (mtDNA). Here we tested whether any of four natural mtDNA variants was able to modify the effect of the phenotypically mild, nuclear tko 25t mutation, affecting mitochondrial protein synthesis. When combined with tko 25t, the mtDNA from wild strain KSA2 produced pupal lethality, accompanied by the presence of melanotic nodules in L3 larvae. KSA2 mtDNA, which carries a substitution at a conserved residue of cytochrome b that is predicted to be involved in subunit interactions within respiratory complex III, conferred drastically decreased respiratory capacity and complex III activity in the tko 25t but not a wild-type nuclear background. The complex III inhibitor antimycin A was able to phenocopy effects of the tko 25t mutation in the KSA2 mtDNA background. This is the first report of a lethal, nuclear-mitochondrial interaction within a metazoan species, representing a paradigm for understanding genetic interactions between nuclear and mitochondrial genotype relevant to human health and disease.